Pattern of cancer in young adults at National Institute of Cancer Research and Hospital (NICRH), Bangladesh - Talukder, MH; Jabeen, S; Shaheen, S; Islam, MJ; Haque, M (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S28-33 The abstract of this article is available on the PubMed website